PEMELIHARAAN SHUTDOWN MEASUREMENT PADA PERALATAN CURRENT TRANSFORMATOR DAN LIGHTNING ARRESTER PADA BAY LINE KUTA 2 GARDU INDUK 150kV SENGKOL. (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING, INFORMATION TECHNOLOGY, CONTROL ENGINEERING, AND ROBOTIC), 2024)
This research aims to find out how and the results of routine 2-year maintenance on current transformers and Lighting Arrester in a state of blackout (shutdown measurement). Tests carried out in the form of testing insulation resistance and grounding resistance. The measuring instrument used in testing insulation resistance, namely Megger MIT 1025 while for testing grounding resistance used Digital Earth Kyoritsu Model 4105A. The results obtained in the insulation resistance test are good with a predetermined standard of 1Mohm per 1kV on the current transformer while on the Lightning Arrester with a predetermined standard of > 1Gohm obtained good results as well so it is feasible to operate. The results of the grounding resistance test on the current transformer are in good condition with a standard of
Keywords: SHUTDOWN MEASUREMENT; CURRENT TRANSFORMATOR; LIGHTNING ARESTER; Tahanan Isolasi; Tahanan Pentanahan